Walk away when the political left turns right - Trepanier, Lee, 1972-; Havers, Grant N., 1965- (Political theory for today., 2019)
This book examines key twentieth-century philosophers, theologians, and social scientists who began their careers with commitments to the political left only later to reappraise or reject those commitments due to changes in the culture, economics, and politics.